Explaining Regional Export Performance in a Developing Country: The Role of Geography and Relative Factor Endowments - Gries, Thomas; Naudé, Wim (Regional Studies)

Entrepreneurship and regional economic growth: towards a general theory of start-ups - Gries, Thomas; Naudé, Wim (Innovation: The European Journal of Social Science Research)

IT Productivity and Aggregation using Income Accounting - Kundisch, Dennis; Mittal, N.; Nault, B. (10th Workshop on Information Systems and Economics (WISE))

Enhancing the Quality of Financial Advice with Web 2.0 - An Approach considering Social Capital in the private Asset Allocation - Kundisch, Dennis; Zorzi, R. (Proceedings of the 15th Amercas Conference on Information Systems (AMCIS))

An Evaluation Framework for Tracker Certificates during the Financial Crisis and beyond - Kundisch, Dennis; Klein, C. (International Federation of Classification Societies 2009 Conference)

Technical Analysis as a Method of Risk Management - Dorfleitner, G.; Klein, C.; Kundisch, Dennis (Monetary Growth: Trends, Impacts and Policies)

Proceedings of the 4th International Workshop on Enterprise Applications and Services in the Finance Industry

Who Owns the Customer? Disentangling Customer Loyalty in Indirect Distribution Channels - Eggert, A; Henseler, J; Hollmann, S (Proceedings of the 17th International Colloquium in Relationship Marketing)

Can Successful Customer Acquisition Hurt the Existing Customer Base? - Woisetschläger, D; Garnefeld, I; Eggert, A (Proceedings of the 2009 AMA Summer Marketing Educators' Conference)

Referral reward programs: New customer acquisition by opportunism? - Garnefeld, I; Münkhoff, E; Hogreve, J; Eggert, A (Proceedings of the 15th Academy of Marketing Science (AMS) World Marketing Congress)

Musing on a Decade of Customer Value Research in Business Relationships: Where Do We Come From? Where Should We Go? - Eggert, A; Ulaga, W (Proceedings of the 4th International Conference on Business Market Management)

Customer Referral Programs and Customer Retention – Do Rewards Undermine the Retention Effect? - Garnefeld, I; Helm, S; Tax, S; Eggert, A (Proceedings of the 2009 AMA Winter Educators' Proceedings)

Unintended effects of referral reward programs: Exploring the impact of rewards on opportunistic behavior - Garnefeld, I; Münkhoff, E; Hogreve, J; Eggert, A (Proceedings of the 38th European Marketing Academy (EMAC) Conference)

Who Owns the Customer? Exploring Customer Loyalty in a Channel Context - Eggert, A; Henseler, J; Hollmann, S (Proceedings of the 38th European Marketing Academy (EMAC) Conference)

Acceptance of Remote Services – Perception, Adoption, and Continued Usage in Organizational Settings - Wünderlich, Nancy
The increasing employment of information and communication technologies in companies and households has led to considerable changes in the way services are conceived, developed, and delivered. Nancy V. Wünderlich employs a multi-method approach comprising an international qualitative study in Germany, USA and China and a longitudinal quantitative study to analyze remote services. She develops the Interactive Technology-Mediated Service Model (ITSUM) to provide a comprehensive approach of explaining both initial acceptance and repeated, continued usage of remote services in organizations. Finally, she derives managerial implications for remote service providers on how to increase remote service acceptance among their customers and facilitate the export of remote services.

Vorteil Interim Management - Kabst, Rüdiger; Thost, W; Isidor, R

Was zeichnet den erfolgreichen Interim Manager aus? - Kabst, Rüdiger; Isidor, R; Thost, W; Linné, H

Manager auf Zeit: Ignoriert oder akzeptiert? - Kabst, Rüdiger; Isidor, R; Thost, W; Nagel, R

International Fachkräfte gewinnen - Kabst, Rüdiger; Salow, S; Baum, M

Editorial: Motivieren trotz Krise - Kabst, Rüdiger

Editorial: Zukunft sichern - Kabst, Rüdiger

International komparatives Personalmanagement: Evidenz, Methodik & Klassiker des "Cranfield Projects on International Human Resource Management" - Kabst, Rüdiger; Giardini, A; Wehner, M C

Ausgewählte Stichwörter zum internationalen Personalmanagement - Kabst, Rüdiger; Giardini, A (Vahlens großes Personal Lexikon)

Das Cranfield Project on International Strategic Human Resource Management: Eine Einführung - Kabst, Rüdiger; Giardini, A; Wehner, M C (International komparatives Personalmanagement: Evidenz, Methodik & Klassiker des “Cranfield Projects on International Human Resource Management”)

Das Lernverhalten früh internationalisierender Unternehmen: ein konzeptioneller Analyserahmen. - Schwens, C; Kabst, Rüdiger (Internationale Unternehmensführung - Entscheidungsfelder und politische Aspekte.)

Die deutsche Cranet-Erhebung 2005: Empirische Befunde und Ergebnisbericht - Kabst, Rüdiger; Giardini, A (International komparatives Personalmanagement: Evidenz, Methodik & Klassiker des “Cranfield Projects on International Human Resource Management”)

A typology of international new ventures: Empirical evidence from high technology industries. - Baum, M; Schwens, C; Kabst, Rüdiger

Determinanten der Gründungsintention – Eine empirische Analyse unter Einbeziehung der Theory of Planned Behaviour [Determinants of the founding intention – An empirical analysis based on the theory of planned behavior] - Zapkau, F B; Steinmetz, Holger; Schwens, C; Kabst, Rüdiger

Employer image and the intention to apply: A cross-national analysis - Baum, M; Kabst, Rüdiger

International Joint Venture Performance: - Isidor, R; Steinmetz, Holger; Schwens, C; Kabst, Rüdiger

The effects of FDI on employment within the domestic market: The moderating role of ownership structures - Zapkau, F B; Schwens, C; Kabst, Rüdiger

The interplay of knowledge intensity, international networks and experience on the type of international new venturing - Baum, M; Schwens, C; Kabst, Rüdiger

Determinanten der Gründungsintention – Eine empirische Analyse unter Einbeziehung der Theory of Planned Behaviour [Determinants of the founding intention – An empirical analysis based on the theory of planned behavior] - Zapkau, F B; Steinmetz, Holger; Schwens, C; Kabst, Rüdiger

Employer image and the intention to apply: A cross-national analysis - Baum, M; Kabst, Rüdiger

International Joint Venture Performance: A Meta-Analytical Structural Equation Model - Isidor, R; Steinmetz, Holger; Schwens, C; Kabst, Rüdiger

The effects of FDI on employment within the domestic market: The moderating role of ownership structures - Zapkau, F B; Schwens, C; Kabst, Rüdiger

The interplay of knowledge intensity, international networks and experience on the type of international new venturing - Baum, M; Schwens, C; Kabst, Rüdiger

Lernkulturen an Hochschulen: Theoretische Überlegungen zur Betrachtung studentischen Lernens unter individueller, pädagogischer und organisationaler Perspektive - Jenert, Tobias; Zellweger, Franziska; Dommen, Jenny; Gebhardt, Anja
Keywords: Lernkultur; Hochschule; HEI; learning culture; higher education; teaching and learning; Hochschullehre

Prüfungskulturgestalten?!: Prozess- und Qualitätsunterstützung schriftlicher Prüfungen an Hochschulen durch eine Web-Applikation - Jenert, Tobias; Zellweger , Franziska; Meier, Christoph (E-Learning 2009 - Lernen im Digitalen Zeitalter)

A simple bootstrap bandwidth selector for local polynomial fitting - Feng, Yuanhua; Heiler, Siegfried (Journal of Statistical Computation and Simulation)

Modifying the double smoothing bandwidth selector in nonparametric regression - Beran, Jan; Feng, Yuanhua; Heiler, Siegfried (Statistical Methodology)

Benchmarking the impact of customer share in key-supplier relationships - Eggert, Andreas; Ulaga, Wolfgang; Hollmann, Sabine (Journal of Business & Industrial Marketing)

Did the Hartz Reforms speed-up the matching process? A macro-evaluation using empirical matching functions - Fahr, René; Sunde, Uwe (German economic review)

Gender differentials in skill use and skill formation in the aftermath of vocational training - Fahr, Rene; Sunde, Uwe (Applied Economics Letters)

Modeling the Impact of Corporate Reputation on Customer Satisfaction and Loyalty Using Partial Least Squares - Helm, Sabrina; Eggert, Andreas; Garnefeld, Ina (Handbook of Partial Least Squares)

Triggers of HR outsourcing decisions--an empirical analysis of German firms - Alewell, Dorothea; Hauff, Sven; Thommes, Kirsten; Weiland, Katrin (The International Journal of Human Resource Management)

Paderborner Forschungs- und Entwicklungswerkstatt - Forschungsfragen und -konzepte der beruflichen Bildung

Bildungsperspektiven in alternden Gesellschaften

Praxisphasen in beruflichen Entwicklungsprozessen - Kremer, H.-Hugo; Tramm, T.; Siemon, J. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Schülerbetriebspraktikum im Übergangssystem - Relevanz, Potenziale und Gestaltungsanforderungen - Kremer, H.-Hugo; Gockel, C. (bwp@ Ausgabe 17, Praxisphasen in beruflichen Entwicklungsprozessen)